State Liability to Fulfillment of Water Rights In Improving Public Health Degrees - Lumunon, Theodorus H. W. (LEX ET SOCIETATIS, 2021)
This research identifies the principles of State Liability for the fulfillment of the Water Rights in improving the public health degree and analyzes the State Liability under the principles of water rights, under human rights law and the concept of public health. The results of research indicate that as an independent right, the right to water is expressly recognized in international law and implied by the 1945 Constitution of The Republic Of Indonesia, so that this right is a real and concrete legal right. States liability for the fulfillment of the right to water and specifically for the fulfillment of the minimum water level of the right to water is a non derogable right so that the state is liability. The right to water is ambiguous, has links to the right to health and the right to life. By the nature of the ambiguity, this right has a strong legal position. Indonesia has ratified the International Convenant on Economic, Social and Cultural Right (ICESCR) and accepted the United Nations (UN) Declaration on the right to water and sanitation, thus assuming responsibility for implementing the principles of water rights. Countries may be sued by courts for human rights violations of water because by law materially the right to water has been accepted as an international customary law. Violations of international law are not limited to the most serious human rights violations, but also include human rights violations in all sectors of life of the international community.Â Keywords: State Liability; Water Rights; Public Health Degrees